Mediators of neutrophil function in children with protracted bacterial bronchitis - Baines, Katherine J; Upham, John W; Yerkovich, Stephanie T; Chang, Anne B; Marchant, Julie M; Carroll, Melanie; Simpson, Jodie L; Gibson, Peter G (Chest, 2014)
Protracted bacterial bronchitis (PBB) is a common and treatable cause of chronic wet cough in children in which the mechanisms are not understood. This study investigates the IL-1 pathway and a neutrophil gene expression signature in PBB. BAL was collected from children in an experimental cohort (n = 21, PBB; n = 33, control subjects), and a second validation cohort (n = 36, PBB; n = 11, control subjects). IL-1β, IL-1 receptor antagonist (IL-1RA), and α-defensins 1-3 were assayed by enzyme-linked immunosorbent assay, western blot, and quantitative real-time polymerase chain reaction, together with selected IL-1 pathway members and neutrophil-related molecules. In the experimental cohort, children with symptomatic PBB had significantly higher levels of IL-1β and α-defensin gene and protein expression. Expression of the neutrophil chemokine receptor C-X-C motif receptor 2 was also higher in PBB. IL-1RA protein was higher, however, the IL-1RA:IL-1β ratio was lower in children with PBB than control subjects. In the validation cohort, protein and gene expression of IL-1β and α-defensins 1-3 were confirmed higher, as was gene expression of IL-1 pathway members and C-X-C motif receptor 2. IL-1β and α-defensin 1-3 levels lowered when PBB was treated and resolved. In children with recurrent PBB, gene expression of the IL-1β signaling molecules pellino-1 and IL-1 receptor-associated kinase 2 was significantly higher. IL-1β protein levels correlated with BAL neutrophilia and the duration and severity of cough symptoms. IL-1β and α-defensin 1-3 levels were highly correlated. PBB is characterized by increased IL-1β pathway activation. IL-1β and related mediators were associated with BAL neutrophils, cough symptoms, and disease recurrence, providing insight into PBB pathogenesis.